2019
DOI: 10.2147/ijn.s192699
|View full text |Cite
|
Sign up to set email alerts
|

<p>Electrospun polycaprolactone/collagen nanofibers cross-linked with 1-ethyl-3-(3-dimethylaminopropyl) carbodiimide/<em>N-</em>hydroxysuccinimide and genipin facilitate endothelial cell regeneration and may be a promising candidate for vascular scaffolds</p>

Abstract: Purpose: A promising vascular scaffold must possess satisfying mechanical properties, great hemocompatibility, and favorable tissue regeneration. Combining natural with synthetic materials is a popular method of creating/enhancing such scaffolds. However, the effect of additional modification on the materials requires further exploration. Materials and methods: We selected polycaprolactone (PCL), which has excellent mechanical properties and biocompatibility and can be combined with collagen. Electrospun fiber… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(16 citation statements)
references
References 60 publications
1
14
0
1
Order By: Relevance
“…Protein spectra are characterized by amide stretching and bending vibrations. As can be seen, there is no noticeable shift in the amide peaks among the spectrum patterns of the amniotic membrane powder and the HAMF film, indicating that there were no major changes in the functional groups and the nativity of the proteins such as collagen molecules before and after dissolution 21 , 23 .
Figure 2 FTIR spectra of the amniotic membrane powder and the film resulting from its dissolution in the solvent FA/AA (70/30).
…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…Protein spectra are characterized by amide stretching and bending vibrations. As can be seen, there is no noticeable shift in the amide peaks among the spectrum patterns of the amniotic membrane powder and the HAMF film, indicating that there were no major changes in the functional groups and the nativity of the proteins such as collagen molecules before and after dissolution 21 , 23 .
Figure 2 FTIR spectra of the amniotic membrane powder and the film resulting from its dissolution in the solvent FA/AA (70/30).
…”
Section: Resultsmentioning
confidence: 95%
“…3.2 , which can increase the voltage between the positive and negative poles, which forces the jet to spray lower diameter fibers. Several studies have reported that the combination of PCL and collagen reduces the fiber diameter 23 , 31 . With increasing the HAMP percentage in PCL-20HAMP and PCL-30HAMP, the viscosity and the average diameter of the fibers increased.…”
Section: Resultsmentioning
confidence: 99%
“…Differently from PBS, weight loss did not reach a plateau but steadily increased during the whole period, reaching a maximum of 40% after 28 days. Other research groups report faster rates for PCL/Gel electrospun scaffolds degraded in collagenase solutions, with weight losses around 70–80% after just 14 days (Chen et al, 2019 ; Eskandarinia et al, 2020 ). This discrepancy of results can be explained with the crosslinking strategies that have or have not been adopted.…”
Section: Discussionmentioning
confidence: 97%
“…Polycaprolactone is well known as a strong, non-toxic, low degradable, and semi-crystalline polymer. 9,10 Despite the advantages of PCL, but due to the lack of elasticity, it has limitations in STE applications in the form of a neat structure. Therefore, hybrid PCL-based structures of a blend of two or more polymers are suggested to overcome the limitations of PCL for successful clinical applications.…”
Section: Introductionmentioning
confidence: 99%